A review of in vitro cell culture testing methods for bioactive glasses and other biomaterials for hard tissue regeneration. Issue 48 (10th November 2020) - Jablonská, Eva; Horkavcová, Diana; Rohanová, Dana; Brauer, Delia S.
Abstract : Bioactive glasses are used to regenerate bone, and when developing new compositions, in vitro cell culture studies are key. As test parameters vary widely, this review provides an overview, helping researchers to select the appropriate ones. Abstract : Bioactive glasses are used to regenerate bone by a mechanism which involves surface degradation, the release of ions such as calcium, soluble silica and phosphate and the precipitation of a biomimetic apatite surface layer on the glass. One major area of bioactive glass research is the incorporation of therapeutically active ions to broaden the application range of these materials. When developing such new compositions, in vitro cell culture studies are a key part of their characterisation. However, parameters of cell culture studies vary widely, and depending on the intended use of bioactive glass compositions, different layouts, cell types and assays need to be used. The aim of this publication is to provide materials scientists, particularly those new to cell culture studies, with a tool for selecting the most appropriate assays to give insight into the properties of interest.